Effect of Kinesio Taping on jumping and balance in athletes: A crossover randomized controlled trial - Nunes, G. S.; de Noronha, M.; Cunha, H. S.; Ruschel, C.; Borges Jr., N. G. (The Journal of Strength and Conditioning Research, 2013)
The purpose of this crossover randomized controlled trial was to verify the effect of Kinesio Taping (KT) applied to the triceps surae with the aim to improve muscle performance during vertical jump (VJ), horizontal jump (HJ), and dynamic balance (DB) in healthy college athletes. The participants were 20 athletes (11 men) who competed in 4 different sports modalities (track and field, handball, volleyball, and soccer). Participants had a mean age of 22.3 ± 3.3 years, mean height of 1.74 ± 0.08 m, and mean body mass of 67.8 ± 10.1 kg. The intervention consisted of applying KT from the origin of the triceps surae to its insertion with the purpose of increasing muscle performance, and the placebo consisted of applying tape with nonelastic properties. There were no significant differences between KT and placebo conditions for height (m) in VJ (KT, 0.18 ± 0.06; placebo, 0.17 ± 0.06; p = 0.14), distance (m) in HJ (KT, 1.48 ± 0.3; placebo, 1.47 ± 0.3; p = 0.40), and DB in distance reached (m) in the star excursion balance test, normalized by lower limb length (anterior: KT, 90.0 ± 6.7; placebo, 89.5 ± 7.5; p = 0.56; posterolateral: KT, 92.5 ± 7.5; placebo, 93.2 ± 5.8; p = 0.52; posteromedial: KT, 98.3 ± 6.7; placebo, 98.7 ± 7.4; p = 0.69). The KT technique was not found to be useful in improving performance in some sports-related movements in healthy college athletes; therefore, KT applied to the triceps surae should not be considered by athletes when the sole reason of the application is to increase performance during jumping and balance.